A solid paraffin-based carbon paste electrode modified with 2-aminothiazole organofunctionalized silica for differential pulse adsorptive stripping analysis of nickel in ethanol fuel - Takeuchi, Regina M.; Santos, Andre L.; Padilha, Pedro M.; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2007)
A solid paraffin-based carbon paste electrode modified with 2-aminothiazole organofunctionalized silica (SiAt-SPCPE) was applied to Ni2+ determination in commercial ethanol fuel samples. The proposed method comprised four steps: (1) Ni2+ preconcentration at open circuit potential directly in the ethanol fuel sample, (2) transference of the electrode to an electrochemical cell containing DMG, (3) differential pulse voltammogram registering and (4) surface regeneration by polishing the electrode. The proposed method combines the high Ni2+ adsorption capacity presented by 2-aminothiazole organofunctionalized silica with the electrochemical properties of the Ni(DMG)2 complex, whose electrochemical reduction provides the analytical signal.All experimental parameters involved in the proposed method were optimized. Using a preconcentration time of 20 min, it was obtained a linear range from 7.5 x 10(-9) to 1.0 x 10(-6) mol L-1 with detection limit of 2.0 x 10(-9) mol L-1. Recovery values between 96.5 and 102.4% were obtained for commercial samples spiked with 1.0 mu mol L-1 Ni2+ and the developed electrode was totally stable in ethanolic solutions. The contents of Ni2+ found in the commercial samples using the proposed method were compared to those obtained by graphite furnace atomic absorption spectroscopy by using the F- and t-test. Neither the F- nor t-values exceeded the critical values at 95% confidence level, confirming that there are not statistical differences between the results obtained by both methods. These results indicate that the developed electrode can be successfully employed to reliable Ni2+ determination in commercial ethanol fuel samples without any sample pretreatment or dilution step. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: nickel; ethanol fuel; solid paraffin-based carbon paste electrodes; organofunctionalized silica; 2-aminothiazole; differential pulse stripping voltammetry